Improved climatic chamber for desiccation simulation - Lozada Catalina; Caicedo Bernardo; Thorel Luc (E3S Web of Conferences, 2016)
The climatic chamber at the Universidad de Los Andes was improved for modeling desiccation in soil layers. This chamber allows the measurement of different environmental variables. In this research, evaporation tests were conducted in water imposing boundary conditions for drying, and then these tests were performed in a soil layer. The soil was prepared from a slurry state and was drying controlling the temperature, the infrared radiation, the wind velocity, and the relative humidity. In the first part of this paper, a description of the climatic chamber, operation ranges and theoretical work principles of the climatic chamber are presented. Then, the second part shows the results for desiccation in water and soil. The desiccation tests performed with the climatic chamber allow simulating all environmental conditions accurately during drying coupling the effect of all environmental variables. As a result, the evaporation rate increases with infrared radiation in soil and water. The rate at the beginning of the desiccation tests in clays is the same as in water. However, this evaporation rate decreases as the soil becomes desiccated.